Integrating Planetary Health into Public Health Education for Sustainable Healthcare Practices - Aboualy, Eman (AUC Knowledge Fountain, 2025)
Introduction: Integrating planetary health in public health education became an urgent global call for action since the WHO announced that the climate change and environmental degradation are the most threat facing the humanity in the recent decades (1). According to that, many countries are developing strategies for counteracting and mitigating the impact of climate change and restore the planetary health. These strategies are including policy drafting and preparing their public health professionals to recognize and address the health effects of environmental change, promote practices for sustainable healthcare. Although Egypt is formulating different policies to cope with and respond to the global action for counteracting the climate change impact, but these efforts are still lacking an essential pillar, which is preparing the health workforce and equip them with the necessary knowledge and skills. This study aims at reaching a consensus on the focus areas of study and competencies required for integration of planetary health into public health education, guided by the global education framework for planetary health. Methodology: The study used Delphi technique to reach agreement from a panel of experts in both disciplines, planetary health and public health, on the main focus areas and competencies to be included in the public health education. Results: The consensus was achieved for specific areas for the following focus area of study: Relationships between biodiversity, ecosystem services, and human health, The health impacts of environmental changes driven by human activity, Resilience and Adaptation, Interdisciplinary Collaboration, One Health Approach, Social Determinants of Health, and the following core competencies: Ecological Literacy, Climate Change Adaptation, Adaptive Management, Community Engagement, Environmental Impact Assessment, Environmental Epidemiology Systems Thinking, Leadership Development, Innovation and Entrepreneurship under the main five domains of the educational framework recognized by the Planetary Health Alliance